Pengaruh Entrepreneurial Marketing Terhadap Kinerja Umkm Sentra Kulit Garut Sukaregang - Azmi Azizah Al Mushowwiru; Sisca Eka Fitria (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2019)
The development of Garut Sukaregang leather center raised significantly. The leather products have been recognized and become one of the best leather products in the world and also become a superior product in West Java. However in its implementation, this creative industry faces many problems, one of them is marketing. Therefore, Sukaregang leather center needs the right marketing strategy to develop this creative industry. One of the approaches that is used by micro small and medium enterprises is entrepreneurial marketing. Through this research, there will be a judgment of perfomance business towards entrepreneurial marketing variable with sub variable proactiveness, innovativeness, calculated risk taking, opportunity focus, customer intensity, resource leverage, and value creation. Other than that, author will indicate the impact of sub variable proactiveness, innovativeness, calculated risk taking, opportunity focus, customer intensity, resource leverage, and value creation towards Garut Sukaregang leather center’s perfomance. This research used quantitative method. The research was conducted by distributing questionnaires to 70 respondens of Garut Sukaregang leather center’s owner. The data of questionnaires was tested using validation and reability. Data was analyzed using SEM PLS 3.0. The result of this research showed that the assesment of innovativeness, customer intensity, and value creation have a significant and positive impact on SMEs perfomance while partial subvariable proactiveness, calculated risk taking, opportunity focus, dan resource leveraging have not significant impact on MSMEs perfomance. In this research we can conclude that entrepreneurial marketing has a postive and significant impact towards Garut Sukaregang leather center MSMEs perfomance 56.8%.